Methylene blue in sepsis and septic shock: a systematic review and meta-analysis - Ballarin, Raquel Simões [UNESP]; Lazzarin, Taline [UNESP]; Zornoff, Leonardo [UNESP]; Azevedo, Paula Schmidt [UNESP]; Pereira, Filipe Welson Leal [UNESP]; Tanni, Suzana Erico [UNESP]; Minicucci, Marcos Ferreira [UNESP] (Frontiers, 2024)
Background: Methylene blue is an interesting approach in reducing fluid overload and vasoactive drug administration in vasodilatory shock. The inhibition of guanylate cyclase induced by methylene blue infusion reduces nitric oxide production and improves vasoconstriction. This systematic review and meta-analysis aimed to assess the effects of methylene blue administration compared to placebo on the hemodynamic status and clinical outcomes in patients with sepsis and septic shock. Methods: The authors specifically included randomized controlled trials that compared the use of methylene blue with placebo in adult patients with sepsis and septic shock. The outcomes were length of intensive care unit stay, hemodynamic parameters [vasopressor use], and days on mechanical ventilation. We also evaluated the abnormal levels of methemoglobinemia. This systematic review and meta-analysis were recorded in PROSPERO with the ID CRD42023423470. Results: During the initial search, a total of 1,014 records were identified, out of which 393 were duplicates. Fourteen citations were selected for detailed reading, and three were selected for inclusion. The studies enrolled 141 patients, with 70 of them in the methylene blue group and 71 of them in the control group. Methylene blue treatment was associated with a lower length of intensive care unit stay (MD −1.58; 95%CI −2.97, −0.20; I2 = 25%; p = 0.03), decreased days on mechanical ventilation (MD −0.72; 95%CI −1.26, −0.17; I2 = 0%; p = 0.010), and a shorter time to vasopressor discontinuation (MD −31.49; 95%CI −46.02, −16.96; I2 = 0%; p < 0.0001). No association was found with methemoglobinemia. Conclusion: Administering methylene blue to patients with sepsis and septic shock leads to reduced time to vasopressor discontinuation, length of intensive care unit stay, and days on mechanical ventilation. Systematic review registration: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023423470, CRD42023423470.
Keywords: meta-analysis; methylene blue; sepsis; septic shock; systematic review